Facial icons as indexes of emotions and intentions - Achour-Benallegue, Amel; Pelletier, Jérôme; Kaminski, Gwenaël; Kawabata, Hideaki (Frontiers in Psychology, 2024)
Various objects and artifacts incorporate representations of faces, encompassing artworks like portraits, as well as ethnographic or industrial artifacts such as masks or humanoid robots. These representations exhibit diverse degrees of human-likeness, serving different functions and objectives. Despite these variations, they share common features, particularly facial attributes that serve as building blocks for facial expressionsan effective means of communicating emotions. To provide a unified conceptualization for this broad spectrum of face representations, we propose the term "facial icons" drawing upon Peirce's semiotic concepts. Additionally, based on these semiotic principles, we posit that facial icons function as indexes of emotions and intentions, and introduce a significant anthropological theory aligning with our proposition. Subsequently, we support our assertions by examining processes related to face and facial expression perception, as well as sensorimotor simulation processes involved in discerning others' mental states, including emotions. Our argumentation integrates cognitive and experimental evidence, reinforcing the pivotal role of facial icons in conveying mental states."A face is a center of human expression, the transparent envelope of the attitudes and desires of others, the place of manifestation, the barely material support for a multitude of intentions.